A Comparison of Intracochlear Pressures During Ipsilateral and Contralateral Stimulation With a Bone Conduction Implant. Issue 2 (March 2020) - Mattingly, Jameson K.; Banakis Hartl, Renee M.; Jenkins, Herman A.; Tollin, Daniel J.; Cass, Stephen P.; Greene, Nathaniel T.
Abstract : Objectives: To compare contralateral to ipsilateral stimulation with percutaneous and transcutaneous bone conduction implants. Background: Bone conduction implants (BCIs) effectively treat conductive and mixed hearing losses. In some cases, such as in single-sided deafness, the BCI is implanted contralateral to the remaining healthy ear in an attempt to restore some of the benefits provided by binaural hearing. While the benefit of contralateral stimulation has been shown in at least some patients, it is not clear what cues or mechanisms contribute to this function. Previous studies have investigated the motion of the ossicular chain, skull, and round window in response to bone vibration. Here, we extend those reports by reporting simultaneous measurements of cochlear promontory velocity and intracochlear pressures during bone conduction stimulation with two common BCI attachments, and directly compare ipsilateral to contralateral stimulation. Methods: Fresh–frozen whole human heads were prepared bilaterally with mastoidectomies. Intracochlear pressure ( P IC ) in the scala vestibuli ( P SV ) and tympani ( P ST ) was measured with fiber optic pressure probes concurrently with cochlear promontory velocity ( V Prom ) via laser Doppler vibrometry during stimulation provided with a closed-field loudspeaker or a BCI. Stimuli were pure tones between 120 and 10, 240 Hz, and response magnitudes and phases for P IC and V Prom were measured for air and bone conducted sound presentation. Results: Contralateral stimulation produced lower response magnitudes and longer delays than ipsilateral in all measures, particularly for high-frequency stimulation. Contralateral response magnitudes were lower than ipsilateral response magnitudes by up to 10 to 15 dB above 2 kHz for a skin-penetrating abutment, which increased to 25 to 30 dB and extended to lower frequencies when applied with a transcutaneous (skin drive) attachment. Conclusions: Transcranial attenuation and delay suggest that ipsilateral stimulation will be dominant for frequencies over 1 kHz, and that complex phase interactions will occur during bilateral or bimodal stimulation. These effects indicate a mechanism by which bilateral users could gain some bilateral advantage. Abstract : Supplemental Digital Content is available in the text.